Reading habits pf Algerians during the COVID-19 Lockdown period - عزيزي, سهيلة; Boufidjline, Zohra (Journal of Library Science, 2022)
This study aims to evaluate Algerians’ reading preferences during the COVID-19 lockdown and find whether there is a correlation between reading habits and certain demographic factors. A descriptive survey design was adopted and a simple random sampling technique was used. To meet this endeavour, a web-based questionnaire was administered owing to the risk of paper and the total number of responses collected was 1002. Results revealed that Algerians’ reading habits were significantly improved during the lockdown. It was shown that, despite Algerians’ growing digital reading habits during the period of lockdown, readers still prefer reading on paper since it is more comfortable, and at that time, homes were the most popular reading locations.
Keywords: Reading habits; reading attitudes; Lockdown; COVID-19 pandemic; Algerian readers